A Comprehensive Review on the Therapeutic Potential of Curcuma longa Linn. in Relation to its Major Active Constituent Curcumin - Fuloria, Shivkanya; Mehta, Jyoti; Chandel, Aditi; Sekar, Mahendran; Rani, Nur Najihah Izzati Mat; Begum, M. Yasmin; Subramaniyan, Vetriselvan; Chidambaram, Kumarappan; Thangavelu, Lakshmi; Nordin, Rusli; Wu, Yuan Seng; Sathasivam, Kathiresan V.; et al. (Frontiers in Pharmacology, 2022)
Graphical Abstract